Pulse thermography-based ageing assessment of thin thermal barrier coatings. - Tinsley, Lawrence (Cranfield University, 2019)
With the motivation to drive gas turbines at increasing power and efficiency, the increase of combustion temperatures is highly desirable, while turbine temperatures are met by material limitations where the temperatures readily exceed the melting point of the metals used to make the components. In response to this, engine manufacturers implement thermal control systems, from air cooling of the component, to Thermal Barrier Coatings (TBCs) applied on the component surfaces, reflecting radiant heat energy and providing an insulating layer. These materials reduce the temperature experienced by the component materials, enabling higher operational temperatures; while the metallic bond coat in between also protects against oxidation and corrosion attack. With TBCs playing such a crucial role in the standard operation of gas turbines at the edge of its performance capability, standing between materials performing one of the most stringent engineering roles ever designed, and the hot gases capable of melting them; the durability of the TBC to resist its own degradation and their ensuing material life are vital. The assessment of TBC health and its Remaining Useful Life (RUL) are of key interest in the maintenance of aero engine components. This thesis presents a review of Non-Destructive Testing (NDT) methods utilised in the inspection of TBCs, proceeding to evaluate the use of pulsed-active flash thermography NDT for ageing assessment of thin TBCs undergoing cyclic oxidation ageing, selected for study to adapt the method to the more challenging context at the cutting edge of gas turbine performance. The coatings were inspected with and without emissivity-improving soot coating to evaluate a realistic inspection scenario – where contamination may not be justifiable – with ideal inspections performed in parallel. In order to address the challenge of capturing a fast thermal event through a thin TBC, an inspection framework was developed to optimise the data capture and analysis parameters. Through-depth diffusivity has been measured during oxidation ageing of six 150µm thick TBCs deposited via Electron Beam Physical Vapour Deposition (EB-PVD), showing a repeatable trend with distinct features, which can be exploited for ageing characterisation, with automation of thermographic NDT of TBC parts demonstrating the potential for rapid implementation of the technique. The research provides through-life captures of each of the TBC samples uniquely coupled with parallel captures in the non-ideal inspection condition without application of an emissivity improving soot coating, simulating a real-world inspection scenario in which a wide area un-treated surface inspection is desired. Additionally, a novel inspection framework has been developed for establishing the multiple coupled parameters required to tackle the complexities introduced when applying optical flash for thermography of thin EB-PVD TBCs.
Keywords: Non-destructive testing; degradation lifing assessment; thermographic inspection; remaining useful life; thermal barrier coatings; gas turbines